2014
DOI: 10.1002/app.41743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propylene carbonate on the ionic conductivity of polyacrylonitrile‐based solid polymer electrolytes

Abstract: Solid polymer electrolyte membranes consisting of polyacrylonitrile (PAN) as a host polymer, ammonium nitrate (NH4NO3) as a complexing salt, and propylene carbonate (PC) as a plasticizer were prepared by a solution casting technique. An increase in the amorphous nature of the polymer electrolytes was confirmed by X‐ray diffraction analysis. A shift in the glass‐transition temperature of the PAN/NH4NO3/PC electrolytes was observed in the differential scanning calorimetry thermograms; this indicated interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The crystallinity of the 30 wt% SN is significantly lower compared with other electrolyte films. This decrease in the crystallinity caused a reduction in the energy barrier to the segmental motion of the polymer electrolyte [22]. Figure 4 shows the DSC thermograms of pure PEO, PEO 20 -LiTDI, PEO 20 -LiTDI-20 % SN and PEO 20 -LiTDI-30 % SN polymer electrolytes in the temperature range -100 to 100°C.…”
Section: Xrd Analysismentioning
confidence: 98%
“…The crystallinity of the 30 wt% SN is significantly lower compared with other electrolyte films. This decrease in the crystallinity caused a reduction in the energy barrier to the segmental motion of the polymer electrolyte [22]. Figure 4 shows the DSC thermograms of pure PEO, PEO 20 -LiTDI, PEO 20 -LiTDI-20 % SN and PEO 20 -LiTDI-30 % SN polymer electrolytes in the temperature range -100 to 100°C.…”
Section: Xrd Analysismentioning
confidence: 98%
“…This prevention results in higher transportation of triiodide toward the counter electrode and a higher rate of reduction from triiodide to iodide ions. Furthermore, the presence of ILs also augments the diffusivity and conductivity by decreasing the viscosity and crystalline nature of polymer matrix by forming complexation with polymer chains. , Thermal analysis and XRD analysis confirmed that the presence of ILs lowers the glass transition temperature and crystalline intensity of the gel. This increment of amorphous percentages of gel and reduction of viscosity promotes the spreading of polymer over photoanode yielding a longer electron lifetime. ,, The combined effect of aforementioned properties of ILs enhances the performance of biopolymer electrolytes with the increment of ILs concentration as displayed in Figure a.…”
Section: Factors That Influence the Performance Of The Biopolymer-bas...mentioning
confidence: 83%
“…Furthermore, the presence of ILs also augments the diffusivity and conductivity by decreasing the viscosity and crystalline nature of polymer matrix by forming complexation with polymer chains. 290,409 Thermal analysis and XRD analysis confirmed that the presence of ILs lowers the glass transition temperature and crystalline intensity of the gel. This increment of amorphous percentages of gel and reduction of viscosity promotes the spreading of polymer over photoanode yielding a longer electron lifetime.…”
Section: Factors That Influence the Performancementioning
confidence: 85%
“…The T g in RNa-9 decreases after addition of ionic liquid maybe due to increase of polymer flexibility, higher amorphous phase, and possibility of reduction in the internal viscosity due to addition of MPII ionic liquid [30,31].…”
Section: Accepted Manuscriptmentioning
confidence: 98%